Albumin competitively inhibits glycation of less abundant proteins - Bhonsle, Hemangi S.; Singh, Sameer Kumar; Srivastava, Ghanshyam; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Protein and Peptide Letters, 2008)
Glycation, a non-enzymatic reaction between glucose and protein is the primary cause of diabetic complications. Albumin, the most abundant plasma protein undergoes glycation both in vivo and in vitro. The influence of albumin on glycation of less abundant proteins has not been addressed. For the first time, we show that albumin competitively inhibits the glycation of less abundant proteins. This study suggests that at least in the initial stages of diabetes, albumin may protect other proteins from glycation.
Keywords: Diabetes; glucose; insulin; MALDI-TOF-MS; vascular complication

Discovery of rifampicin as a new anti-glycating compound by matrix-assisted laser desorption/ionization mass spectrometry-based insulin glycation assay - Golegaonkar, Sandeep B.; Bhonsle, Hemangi S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (European Journal of Mass Spectrometry, 2010)
An in vitro insulin glycation assay was developed for screening glycation inhibitors. The assay involves the use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for monitoring the formation of glycated insulin. The assay is simple, rapid and amenable for high throughput screening. Using this assay we have discovered a strong anti-glycation activity for the anti-tuberculosis drug rifampicin. These results were compared with bovine serum albumin glucose fluorescence assay. In addition, the IC(50) of rifampicin was lower than that of aminoguanidine, a known anti-glycating agent, suggesting that rifampicin is a more potent glycation inhibitor.
Keywords: AGE; aminoguanidine; antibiotic; diabetic complication; drug repositioning; IC(50)

Analysis of AGE modified proteins and RAGE expression in HER2/neu negative invasive ductal carcinoma - Korwar, Arvind M.; Bhonsle, Hemangi S.; Chougale, Ashok D.; Kote, Sachin S.; Gawai, Kachru R.; Ghole, Vikram S.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (Biochemical and Biophysical Research Communications, 2012)
Cancer is associated with increased glycolysis and carbonyl stress. In view of this, AGE modified proteins were identified from clinical breast cancer tissue using 2DE-immunoblot and mass-spectrometry. These proteins were identified to be serotransferrin, fibrinogen gamma chain, glycerol-3-phosphate dehydrogenase, lactate dehydrogenase, annexin II, prohibitin and peroxiredoxin 6, which have established role in cancer. Further, RAGE expression and its downstream signaling proteins NADPH oxidase and NF-kB were studied. Role of these AGE modified proteins and RAGE signaling in breast cancer is discussed. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: advanced glycation end products; Breast cancer; RAGE

Low plasma albumin levels are associated with increased plasma protein glycation and HbA1c in diabetes - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kote, Sachin S.; Golegaonkar, Sandeep B.; Chougale, Ashok D.; Shaik, Mahemud L.; Dhande, Nitin L.; Giri, Ashok P.; Shelgikar, Kishore M.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Journal of Proteome Research, 2012)
Albumin is one of the most abundant plasma proteins and is heavily glycated in diabetes. In this study, we have addressed whether variation in the albumin levels influence glycation of plasma proteins and HbA1c. The study was performed in three systems: (1) streptozotocin (STZ)-induced diabetic mice plasma, (2) diabetic clinical plasma, and (3) in vitro glycated plasma. Diabetic mice and clinical plasma samples were categorized as diabetic high albumin plasma (DHAP) and diabetic low albumin plasma (DLAP) on the basis of their albumin levels. For the in vitro experiment, two albumin levels, high albumin plasma (HAP) and low albumin plasma (LAP), were created by differential depletion of plasma albumin. Protein glycation was studied by using a combination of two-dimensional electrophoresis (2DE), Western blotting, and LC-MSE. In both mice and clinical experiments, an increased plasma protein glycation was observed in DLAP than in DHAP. Additionally, plasma albumin levels were negatively correlated with HbA1c. The in vitro experiment with differential depletion of albumin mechanistically showed that the low albumin levels are associated with increased plasma protein glycation and that albumin competes for glycation with other plasma proteins.
Keywords: advanced glycation end products (AGEs); Albumin; glucose; post translational modification

Zoom-in - a targeted database search for identification of glycation modifications analyzed by untargeted tandem mass spectrometry - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kesavan, Suresh K.; Bhosale, Santosh D.; Bansode, Sneha B.; Kulkarni, Mahesh J. (European Journal of Mass Spectrometry, 2012)
Post-translational modifications (PTMs) are very important to biological function, however their identification and characterization is technically challenging. In this study, we have identified glycation modifications by nano LC-MSE, a data independent acquisition work flow, followed by database search using the Protein Lynx Global Server (PLGS). PLGS search with a complete human protein database hardly identified glycation modifications in a glycated human serum albumin (HSA), which was detected to be glycated by western blotting with advanced glycation end products (AGE) antibody and fluorescence spectroscopy. To overcome this difficulty, ``Zoom-In'' approach, a targeted database search was used to identify glycation modifications in a glycated HSA, which were further manually validated. This approach was useful for identification of glycation modifications from untargeted tandem mass spectrometry workflow such as MSE, but may require the development of a new algorithm or an upgrade of the existing software.
Keywords: advanced glycation end products (AGEs); data independent acquisition; Diabetes; post-translational modifications

Arsenomics of exiguobacterium sp PS (NCIM 5463) - Sacheti, Poonam; Bhonsle, Hemangi S.; Patil, Rajendra; Kulkarni, Mahesh J.; Srikanth, Rapole; Gade, Wasudeo N. (RSC Advances, 2013)
In the present study, arsenate [As(V)] tolerant organisms were isolated from a metal contaminated site, and identified by 16S rDNA sequencing as Exiguobacterium sp. Arsenomics (omics of arsenic response) in Exiguobacterium sp. PS via two-dimensional gel electrophoresis (2-DGE) coupled with identification of proteins using MALDI-TOF MS, MALDI-TOF MS/MS and LC/MSE are studied vide this paper. Out of 2460 Coomassie stained proteins, 270 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 45 spots (proteins) were subjected to MALDI-TOF MS/MS, MALDI-TOF/TOF and LC/MSE. Out of these, 33 were identified and categorized into several functional categories (including both known and novel/putative stress responsive proteins) viz., carbohydrate and energy metabolism, stress response, motility, amino acid, and purine and protein synthesis. The identifications of unique proteins, phosphate ABC transporter ATPase subunit and pyridine nucleotide disulfide oxidoreductase, are the significant findings of the present study which may be used as markers of As(V) stress in Exiguobacterium sp. PS. The absence of As(V) reductase activity and non-amplification of the arsC gene of the ars operon suggests that the classical mechanism of As(V) resistance may not be operating in Exiguobacterium sp. PS. Lastly, considering the fact that proteomic studies under As(V) stress were performed only in Gram negative organisms, this study is the first comprehensive endeavour to explore the mechanism of As(V) response in Gram positive organisms, Exiguobacterium sp. PS at the proteomic level.

Glycated proteome: from reaction to intervention - Kulkarni, Mahesh J.; Korwar, Arvind M.; Mary, Sheon; Bhonsle, Hemangi S.; Giri, Ashok P. (Proteomics Clinical Applications, 2013)
Glycation, a nonenzymatic reaction between reducing sugars and proteins, is a proteome wide phenomenon, predominantly observed in diabetes due to hyperglycemia. Glycated proteome of plasma, kidney, lens, and brain are implicated in the pathogenesis of various diseases, including diabetic complications, neurodegenerative diseases, cancer, and aging. This review discusses the strategies to characterize protein glycation, its functional implications in different diseases, and intervention strategies to protect the deleterious effects of protein glycation.
Keywords: aging; Diabetes; Glycation; RAGE

Proteomic profiling and interactome analysis of ER-positive/HER2/neu negative invasive ductal carcinoma of the breast: towards proteomics biomarkers - Korwar, Arvind M.; Bhonsle, Hemangi S.; Ghole, Vikram S.; Gawai, Kachru R.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (OMICS-A Journal of Integrative Biology, 2013)
Breast cancer, especially ER positive/HER2/neu negative IDC, is the predominant subtype of invasive ductal carcinoma. Although proteomic approaches have been used towards biomarker discovery in clinical breast cancer, ER positive/HER2/neu negative IDC is the least studied subtype. To discover biomarkers, as well as to understand the molecular events associated with disease progression of estrogen receptor positive/HER2/neu negative subtype of invasive ductal carcinoma, differential protein expression profiling was performed by using LC-MSE (MS at elevated energy). A total of 118 proteins were identified, of which 26 were differentially expressed. These identified proteins were functionally classified and their interactions and coexpression were analyzed by using bioinformatic tools PANTHER (Protein Analysis THrough Evolutionary Relationships) and STRING (Search Tool for the Retrieval of Interacting Genes). These proteins were found to be upregulated and were involved in cytoskeletal organization, calcium binding, and stress response. Interactions of annexin A5, actin, S100 A10, glyceraldehyde 3 phosphate dehydrogenase, superoxide dismutase 1, apolipoprotein, fibrinogen, and heat shock proteins were prominent. Differential expression of these proteins was validated by two-dimensional gel electrophoresis and Western blot analysis. The cluster of these proteins may serve as a signature profile for estrogen receptor positive/ HER2/neu negative subtype.

Proteomic study reveals downregulation of apolipoprotein A1 in plasma of poorly controlled diabetes: a pilot study - Bhonsle, Hemangi S.; Korwar, Arvind M.; Chougale, Ashok D.; Kote, Sachin S.; Dhande, Nitin L.; Shelgikar, Kishore M.; Kulkarni, Mahesh J. (Molecular Medicine Reports, 2013)
Proteomic approaches aid in gaining a better understanding of the pathophysiology of diabetic complications. In view of this, differential protein expression in diabetic plasma samples was studied by a combination of proteomic and western blot analyses. Diabetic plasma samples were categorized based on glycated haemoglobin levels as controlled diabetes (CD; 7-8%), poorly controlled diabetes (PCD; >8%) and non-diabetic control (ND;<6.4%). Two-dimensional electrophoresis and liquid chromatography-mass spectrometry revealed differential expression of proteins including upregulation of fibrinogen and haptoglobin and downregulation of vitamin D binding protein, alpha-1-antitrypsin, transthyretin and apolipoprotein A1 (Apo A1) in diabetic compared with non-diabetic plasma samples. Amongst these proteins, Apo A1 downregulation was prominent in PCD. Downregulation of Apo A1 may serve as an early predictive marker of diabetic complications.
Keywords: biomarker; HbA1c; proteomics

Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics

Mass spectrometry based identification of galectin-3 interacting proteins potentially involved in lung melanoma metastasis - Dange, Manohar C.; Bhonsle, Hemangi S.; Godbole, Rashmi K.; More, Shyam K.; Bane, Sanjay M.; Kulkarni, Mahesh J.; Kalraiya, Rajiv D. (Molecular Biosystems, 2017)
Adhesive interactions between molecules on tumor cells and those on target organs play a key role in organ specific metastasis. Poly-N-acetyl-lactosamine (polyLacNAc) substituted N-oligosaccharides on melanoma cell surface glycoproteins promote lung specific metastasis via galectin-3 by facilitating their arrest and extravasation. This study reports the identification and characterization of galectin-3 interacting proteins using a combination of galectin-3 sepharose affinity and leucoagglutinating phytohemagglutinin (L-PHA) columns. A total of 83 proteins were identified as galectin-3 interacting glycoproteins, of which 35 were constituents of the L-PHA bound fraction, suggesting that these proteins carry polyLacNAc substituted beta 1,6 branched N-glycans. The identities of some of these proteins, like LAMP-1, LAMP-3, basigin, embigin, and alpha 5 and beta 1 Integrin, have been confirmed by western blotting, and functional relevance with respect to metastatic properties has been established.